Identification of a Novel PNMA-MS1 Gene in Marsupials Suggests the LTR Retrotransposon-Derived PNMA Genes Evolved Differently in Marsupials and Eutherians - Iwasaki, Sawa (Oxford University Press, 2013)
Two major gene families derived from Ty3/Gypsy long terminal repeat (LTR) retrotransposons were recently identified in mammals. The sushi-ichi retrotransposon homologue (SIRH) family comprises 12 genes: 11 in eutherians including Peg10 and Peg11/Rtl1 that have essential roles in the eutherian placenta and 1 that is marsupial specific. Fifteen and 12 genes were reported in the second gene family, para-neoplastic antigen MA (PNMA), in humans and mice, respectively, although their biological functions and evolutionary history remain largely unknown. Here, we identified two novel candidate PNMA genes, PNMA-MS1 and -MS2 in marsupials. Like all eutherian-specific PNMA genes, they exhibit the highest homology to a Gypsy12_DR (DR, Danio rerio) Gag protein. PNMA-MS1 is conserved in both Australian and South American marsupial species, the tammar wallaby and grey short-tailed opossum. However, no PNMA-MS1 orthologue was found in eutherians, monotremes or non-mammalian vertebrates. PNMA-MS1 was expressed in the ovary, mammary gland and brain during development and growth in the tammar, suggesting that PNMA-MS1 may have acquired a marsupial-specific function. However, PNMA-MS2 seems to be a pseudogene. The absence of marsupial orthologues of eutherian PNMA genes suggests that the retrotransposition events of the Gypsy12_DR-related retrotransposons that gave rise to the PNMA family occurred after the divergence of marsupials and eutherians.